Kakovosten zrak v pisarnah povečuje produktivnost - Fanger, P. Ole (Strojniški vestnik, 2000)
Three recent independent studies have documented that the quality of indoor air has a significant and positive influence on the productivity of office workers. A combined analysis of the results of the three studies shows a significant relationship between productivity and perceived indoor air quality. The impact on productivity justified a much higher indoor air quality than the minimum levels presribed in present standards and guidelines.One way of providing air of high quality for people to breathe, without involving excessive ventilation rates and energy use, is to provide "personalized air" to each individual. The application of this concept is discussed in this paper.
Keywords: zrak v prostorih; vplivi na produktivnost; ventilacija; kakovost zraka; zrak; kvaliteta; prezračevanje; pisarne